Density Functional Study of Electronic and Structural Properties of Gold-Cadmium Selenide/Telluride Nanoclusters - Shimeles T. Bulbula; Hagos W. Zeweldi (Advances in Materials Science and Engineering)
Semiconductor nanowires are one class of building blocks that show promise for application in nanoscale electronics. Metal-semiconductor nanowire helps to improve the electrical properties or create unique ones. Electronic and structural properties of cadmium selenide/telluride connected to gold electrode clusters have been the focus of this research due to their importance in constructing fast microelectric devices. The simulations were carried out by using VASP (Vienna Ab-Initio Simulation Package) which utilizes the method of density functional theory (DFT) and plane wave basis set. Optimization was performed to obtain the minimum energy structure. In this research paper the result shows that the HOMO-LUMO gaps for the minimum energy cadmium selenide/telluride connected to gold electrodes decrease as cluster size increases, whereas the binding energy shows a reverse relationship with the cluster size. However, a few clusters show special properties like AuCd2Se3 and AuCd2Te3 clusters.